The Combination of Vitamin K-3 and Vitamin C Has Synergic Activity against Forms of Trypanosoma cruzi through a Redox Imbalance Process - Desoti, Vania Cristina; Lazarin-Bidoia, Danielle; Ribeiro, Fabianne Martins; Martins, Solange Cardoso; Silva Rodrigues, Jean Henrique da; Ueda-Nakamura, Tania; Nakamura, Celso Vataru; Ximenes, Valdecir Farias [UNESP]; Silva, Sueli de Oliveira (Public Library Science, 2015)
Chagas' disease is an infection that is caused by the protozoan Trypanosoma cruzi, affecting millions of people worldwide. Because of severe side effects and variable efficacy, the current treatments for Chagas' disease are unsatisfactory, making the search for new chemotherapeutic agents essential. Previous studies have reported various biological activities of naphthoquinones, such as the trypanocidal and antitumor activity of vitamin K-3. The combination of this vitamin with vitamin C exerted better effects against various cancer cells than when used alone. These effects have been attributed to an increase in reactive oxygen species generation. In the present study, we evaluated the activity of vitamin K-3 and vitamin C, alone and in combination, against T. cruzi. The vitamin K-3 + vitamin C combination exerted synergistic effects against three forms of T. cruzi, leading to morphological, ultrastructural, and functional changes by producing reactive species, decreasing reduced thiol groups, altering the cell cycle, causing lipid peroxidation, and forming autophagic vacuoles. Our hypothesis is that the vitamin K-3 + vitamin C combination induces oxidative imbalance in T. cruzi, probably started by a redox cycling process that leads to parasite cell death.